Asumsi Toxic Parenting Pada Hadits Perintah Memukul Anak - Abdul Jalal, Luqman (Jurnal Ilmiah Ilmu Ushuluddin, 2024)
The extremist textualist group understands textually the hadith of the Prophet which tolerates parents hitting ten-year-old children to perform prayers. They understand this hadith text as the final sharia which does not accept changes. The terminology of dharaba in the essential sense, the minimum limit is a physical blow that does not leave an impression and does not cause physical harm. The maximum punishment is ta'zir which has a deterrent effect. Even for those who are ten years old and still refuse to pray, the punishment of beatings may be added, and some argue the death penalty if they continue to resist. This research employs a descriptive analysis method, presenting data from literature studies, books, journals, and articles related to the issue of toxic parenting and the hadith on the command to hit children, and then concludes. The results of this research are analyzed comprehensively and contextually, concluding four things; 1). This hadith is related to a very important Islamic principle, namely the obligation to pray, so the Prophet gave a firm solution in straightforward language. 2). This hadith is an integrative unit with the Prophet's family education pattern which prioritized rewards before punishment, in fact the Prophet never hit his children and grandchildren. 3). In practice, the Prophet taught his family with gentleness and affection, carrying and kissing his children and grandchildren. This is in sharp contrast to the jahiliyah culture which hates girls and buries them alive. 4). The term dharaba has become part of the ulama's discourse, whether it means essence or majazi, some understand it as a metaphorical language style which means firmness and discipline in teaching prayer, and some understand it as a physical blow that doesn't hurt.